Mental fatigue negatively influences manual dexterity and anticipation timing but not repeated high-intensity exercise performance in trained adults - Duncan, M. J.; Fowler, N.; George, O.; Joyce, S.; Hankey, J. (Research in Sports Medicine, 2015)
This study examined the impact of a period of mental fatigue on manual dexterity, anticipation timing and repeated high intensity exercise performance. Using a randomised, repeated measures experimental design, eight physically trained adults (mean age = 24.8 ± 4.1 years) undertook a 40 minute vigilance task to elicit mental fatigue or a control condition followed by four repeated Wingate anaerobic performance tests. Pre, post fatigue/control and post each Wingate test, manual dexterity (Seconds), coincidence anticipation (absolute error) were assessed. A series of two (condition) by six (time) ways repeated measures ANOVAs indicated a significant condition by time interactions for manual dexterity time (p = 0.021) and absolute error (p = 0.028). Manual dexterity and coincidence anticipation were significantly poorer post mental fatigue compared with control. There were no significant differences in mean power between conditions or across trials (all p > 0.05).